Prophet Isa and the miracle of the feast - Khan,saniyasnain (china goodwordbooks, 2024)
In the story "Prophet Isa and the Miracle of the Feast," by Saniyasnain Khan, Prophet Isa (Jesus) and his disciples are presented with a unique challenge. His followers ask him to request a heavenly feast from Allah as a sign of their faith. Isa, initially hesitant, eventually prays for the miracle, and Allah provides a table spread with food as a blessing and a sign, showcasing the power of faith and divine provision